A Two-Month-Old Child with Vascular Ectasia: A Case Report Diagnosed by Molecular Karyotyping - Kendir, Ozlem Tolu; Yilmaz, Hayri Levent; Bozdogan, Sevcan; Bisgin, Atıl; Celik, Tugçe; Surmelioglu, Ozgur; Doran, Figen (Journal of Pediatric Genetics, 2019)
Gastrointestinal angiodysplasia can be encountered in cases with aortic stenosis, inflammatory gastrointestinal conditions, von Willebrand disease or vascular damage, and degenerative changes. Predisposing factors have been described in four adults with vascular ectasia located in the stomach, duodenum, and the distal esophagus. Here, we report a 2-month-old infant with vascular ectasia in the proximal esophagus and diagnosed by molecular karyotyping. This is the first case of vascular ectasia in the proximal esophagus in a pediatric patient.
Keywords: angiodysplasia; vascular ectasia; duplication of chromosome 2; molecular karyotyping